Smear grading and the Mantoux skin test can be used to predict sputum smear conversion in patients suffering from tuberculosis - Saffari, Mahmood; Jolandimi, Hadis Alizadeh; Sehat, Mojtaba; Nejad, Nastarn Vali; Hedayati, Mehrdad; Zamani, Mahbobeh; Ghasemi, Amir (German Medical Science GMS Publishing House, 2017)
Purpose: Smear scores and induration sizes resulting from the PPD (tuberculin purified protein derivative) test can serve as indicators of whether a patient suffering from tuberculosis shows smear conversion or not. Methods: Using microbiological methods smear and sputum tests, patients diagnosed as infected with between 2002 and 2015 were included in this study. All of the assumed factors that may have a role in smear conversion were studied, in addition to the prolongation of tuberculosis. Results: 398 of 512 patients fulfilled all the inclusion criteria and formed the basis of this study. 215 patients (54%) were females and 183 (46%) were males. The median age for both men and women was 36 years. We found a statistically significant difference between the size of induration resulting from the PPD skin test and the rate of non-conversion (=0.002). Further univariate analysis also showed that smear grading and an induration size of ≥10 mm were independently associated with delayed smear conversion. Patients with cavitary lesions showed a higher rate of non-conversion after two months, which was not significant. We could not find any association between some of the variables, such as age, sex, weight, smoking, alcoholism, addictions, respiratory diseases, diabetes mellitus, alternative anti-TB treatment, and smear conversion. Conclusion: Intensified treatment and precautions against transmission should be especially considered for TB patients with high smear grading and an induration size of more than 10 mm.